Government audit and earnings quality of Chinese State-Owned Enterprises - Yang, Xin (2016)
This study examines the effects of government audit on the earnings quality of Chinese State-Owned Enterprises (SOEs) and proposes a new structure of audit for SOEs. Discretionary accruals are used as a proxy to examine earnings quality, which are calculated by using Jones (1991) model. I develop three hypotheses concerning the improvements of earnings quality of SOEs after they were audited by the Chinese National Audit Office (CNAO), by comparing with their previous performances, non-government audited SOEs, and manufacturing industrial peers respectively. Annual data from more than 1,000 firms have been used in the tests, which all obtain the same results which support the assumption that SOEs improve their earnings quality in government-audited years. I also find that due to the inconsistency of government audit over time, SOEs immediately increase their discretionary accruals in the following years after being audited by CNAO. Government audit reports of SOEs are also analysed to rectify serious errors and unearthed mistakes discovered by CNAO on accounting, the violation of regulations, internal management, and corruption, none of which are shown in social audit reports. The tests and analysis imply that government audit should take on more responsibility for the supervision of SOEs, and the proposed structure of the integration of government and social audit may be a solution to improve the earnings quality of SOEs.